Realising the supernatural in Baba Malay folktales: a transitivity analysis - Kit Yee Tang,; Ayeshah Syed, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The examination of Baba Malay folktales enables further exploration of this endangered minority language and provides insight into Peranakan Chinese culture. This paper examines how supernatural elements are realised through linguistic choices in six Baba Malay folktales in the contemporary book Chrita-Chrita Baba (by Kenneth Y.K. Chan). Applying Halliday and Matthiessen’s (2014) transitivity analysis from Systemic Functional Linguistics, the texts were analysed to answer two research questions: 1) How are supernatural themes realised in the Baba Malay folktales through the transitivity categories of process, participant and circumstance, and 2) What transitivity patterns are associated with supernatural characters in these folktales? The transitivity analysis reveals that clauses featuring supernatural entities in subject position predominantly instantiate material processes (e.g., pi ‘go’, bikin ‘make’, kasi ‘give’), positioning these figures as dynamic agents within the narrative. Such representation reflects culturally embedded ideologies attributing agency and causal power to supernatural forces, reinforcing communal views in which the supernatural is perceived as an active and determinative presence in human affairs. The difference found between carrier and token participants in relational clauses suggests that the narrative describes, rather than defines, the supernatural characters. The rare association of temporal and spatial circumstances with supernatural beings also shows their otherworldly nature. This study demonstrates how transitivity choices linguistically construct cultural beliefs about agency and otherworldliness in Baba Malay storytelling. The findings extend current scholarship on Baba Malay and Peranakan Chinese culture by detailing the vocabulary and transitivity patterns through which supernatural elements are represented in the folktales.